Preparation method of mixed type soft and hard carbon material and application of mixed type soft and hard carbon material in sodium ion battery
By filling the asphalt in the pores of polyphosphazene nanotubes and carbonized to prepare a mixed soft and hard carbon material, the cost and environmental pollution of the existing sodium ion battery negative electrode material preparation methods are solved, and efficient sodium ion storage and significantly improved battery performance are achieved.
Patent Information
- Application Number
- CN202510066607.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The existing preparation methods for negative electrode materials of sodium ion batteries have problems such as high cost, environmental pollution and increased experimental steps, which affect the practical application of sodium ion batteries.
The preparation method is adopted to dissolve the asphalt and fill it in the pores of polyphosphazene nanotubes, and then obtain a mixed soft and hard carbon material through carbonization. This method improves conductivity by forming a three-dimensional interconnected graphitized carbon structure after carbonization, and generates closed pores through the surface modification of asphalt and the shrinkage of the carbon skeleton to increase the storage active site of sodium ions.
The conductivity of the negative electrode material of sodium ion battery and the diffusion ability of sodium ions are improved, the specific capacity, rate performance and cycle life are significantly improved, and the solid electrolyte interface is optimized to achieve more efficient sodium ion storage.
Smart Images

Figure CN119858913A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of preparation of negative electrode materials for sodium ion batteries, and in particular to a preparation method of a mixed soft and hard carbon material and application thereof in sodium ion batteries. Background Art
[0002] Sodium-ion batteries have attracted widespread attention in large-scale energy storage due to their abundant sodium resources and cost advantages. However, the current commercial graphite anodes are not suitable for sodium-ion storage due to their thermodynamic instability with sodium ions. Therefore, the development of high-performance negative electrode materials is crucial to promote the commercialization of sodium-ion batteries. Hard carbon (HC) is a form of non-graphitizable carbon with randomly oriented carbon layers and complex and diverse nanodomains, as well as a high proportion of closed nanopores. It is considered to be the most suitable negative electrode material for commercial sodium-ion batteries (SIBs). A large number of studies have emphasized the role of closed pores as a material for accommodating Na + The importance of effective active sites, which helps to improve the low-voltage (≤0.1V) plateau capacity.
[0003] Therefore, the existing technology often uses chemical activation, introduction of templates and metal element catalysis to adjust the closed-cell structure. Although these methods can effectively increase the number and size of closed pores in HC and increase the capacity of the platform area, the high cost, environmental pollution, and additional experimental steps need to be solved, which seriously affects the practical application of sodium-ion batteries. Summary of the invention
[0004] In view of the problems existing in the background technology, the present invention proposes a method for preparing a mixed soft and hard carbon material, wherein asphalt is dissolved and filled into the pores of polyphosphazene nanotubes, and then the mixed soft and hard carbon material is obtained by carbonization.
[0005] Preferably, the specific preparation method is:
[0006] S1. preparing polyphosphazene nanotubes;
[0007] S2. Preparation of polyphosphazene nanotube @ asphalt precursor material: dissolving a certain amount of asphalt in an appropriate amount of solvent; then stirring evenly at room temperature and adding a certain mass ratio of polyphosphazene nanotubes; the mass ratio of asphalt to polyphosphazene nanotubes is controlled at 1:2-1:20; continuing to stir so that the dissolved asphalt diffuses into the pores of the polyphosphazene nanotubes and deposits, thereby obtaining the polyphosphazene nanotube @ asphalt precursor material;
[0008] S3, preparing mixed soft and hard carbon materials: carbonizing the polyphosphazene nanotube@asphalt precursor material obtained in S2 to obtain mixed soft and hard carbon material powder.
[0009] Preferably, the preparation method of the polyphosphazene nanotubes in S1 is: dissolving a certain proportion of hexachlorocyclotriphosphazene and 4,4-dihydroxydiphenyl sulfone in an appropriate amount of tetrahydrofuran, stirring and dissolving into a transparent solution, then adding an appropriate amount of an acid binding agent, and then ultrasonicating at 40°C for 10 hours. After the reaction is completed, washing with acetone and deionized water, centrifuging, and then drying to obtain the polyphosphazene nanotubes.
[0010] Preferably, the solvent in S2 is one or more of tetrahydrofuran, N-methylpyrrolidone, benzene, toluene or carbon tetrachloride, the amount of the solvent is 20-100 ml, and the solution concentration is 5 g / L-10 g / L.
[0011] Preferably, the solvent in S2 is tetrahydrofuran, and after the magnetic stirring is completed, the mixture is heated to 50° C.-100° C. in an oil bath to volatilize the tetrahydrofuran.
[0012] Preferably, the two stirrings in S2 are both magnetic stirring for 10 h.
[0013] Preferably, the carbonization treatment method in S3 is: grind the polyphosphazene nanotube @asphalt precursor material evenly and put it into a corundum crucible, then put the crucible into a high-temperature tube furnace and pass high-purity nitrogen as a protective gas, and heat it at a rate of 1-5°C / min according to actual conditions, raise the temperature to 1300-1600°C for carbonization and keep warm for 1-3h, and naturally cool to room temperature after the reaction is completed. The entire reaction process is carried out in an inert atmosphere, and a mixed soft and hard carbon material powder is obtained after the reaction is completed.
[0014] The present invention further proposes the application of the mixed soft and hard carbon material in sodium ion batteries, and the mixed soft and hard carbon material prepared by the above-mentioned preparation method of the mixed soft and hard carbon material is applied to the preparation of negative electrode materials for sodium ion batteries.
[0015] Preferably, the preparation method comprises: fully mixing and grinding the prepared mixed soft and hard carbon material, conductive carbon black and sodium alginate in a mass ratio of 7:2:1-8:1:1, then transferring to a glass bottle, adding an appropriate amount of deionized water and stirring overnight to form a viscous and evenly dispersed slurry, applying it on a copper foil with a scraper of different thicknesses, then vacuum drying at 80°C for 12h, and punching into 12mm sheets as a negative electrode material for a sodium ion battery; cutting the above-mentioned negative electrode material for a sodium ion battery into circular pole pieces with a diameter of 12mm, and then using the positive electrode material, electrolyte, diaphragm, electrode shell and negative electrode material to assemble a battery.
[0016] Preferably, the selected positive electrode material is sodium sheet; the diaphragm is Whatman GF / D; the electrolyte is 1M NaPF 6 In DIGLYME = 100 Vol% solution.
[0017] Compared with the prior art, the present invention has the following beneficial technical effects:
[0018] The present invention dissolves asphalt and fills it into the pores of polyphosphazene nanotubes, and then obtains a mixed soft and hard carbon material through carbonization. The asphalt acts as a "binder" to connect the dispersed nanotubes together. After carbonization, the three-dimensionally interconnected asphalt is carbonized into graphitized carbon, which improves conductivity, promotes the transmission of electrons in the negative electrode material, and shortens the transmission distance of sodium ions, which is more conducive to the diffusion of sodium ions. At the same time, the asphalt has fewer surface defects. After high-temperature carbonization, the asphalt will repair the defects on the HC surface as a surface coating. At the same time, the contraction and rearrangement of the carbon skeleton will form closed pores at the contact surface of the asphalt and PZS, increasing the active sites for storing sodium ions, thereby increasing the platform capacity in the low-pressure area. The change in specific surface area before carbonization can be known through BET. After filling with asphalt, the specific surface area decreases and the number of micropores is significantly reduced, indicating that the asphalt diffuses into the pores of PZS and repairs surface defects. The specific surface area of the agglomerate after carbonization is also increased from the original 76.6m 2 g -1 Reduced to 5.8m 2 g -1 . The present invention can also adjust the sp2 / sp3 content distribution in HC-XP after carbonization by adjusting the asphalt content. As the asphalt content increases, the ratio of the surface sp2 / sp3 hybridized graphite carbon changes. By adjusting the sp2 / sp3 structure to a coordinated equilibrium state, the optimal solid electrolyte interface (SEI) is obtained in the battery cycle, and the optimal ICE and sodium ion storage capacity are achieved. In addition, since the soft and hard carbon composite materials of the present invention have a large number of closed pores, sp2 / sp3 coordinated balance and surface coating modification, the specific capacity, rate performance and long cycle life of the sodium ion battery negative electrode material based on the material of the present invention are significantly improved, and excellent cycle performance is also obtained after assembling the full battery, showing practicality. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of nitrogen adsorption and desorption of polyphosphazene nanotubes@asphalt precursor material.
[0020] Figure 2 Schematic diagram of the pore size distribution of polyphosphazene nanotube@asphalt precursor material.
[0021] Figure 3 This is the SEM image of mixed soft and hard carbon materials with different asphalt contents after carbonization.
[0022] Figure 4 Schematic diagram of nitrogen adsorption and desorption of HC, HC-30P, and PC after carbonization.
[0023] Figure 5 Schematic diagram of the pore size distribution of HC, HC-30P, and PC after carbonization.
[0024] Figure 6 XPS and Raman images of mixed soft and hard carbon materials with different asphalt contents.
[0025] Figure 7 TEM image of HC.
[0026] Figure 8 This is the TEM image of HC-30P.
[0027] Fig. 9 Schematic diagram of directly mixing and carbonizing the solid phase.
[0028] Fig.10 Schematic diagram of carbonization after dissolution in tetrahydrofuran.
[0029] Fig.11 For different asphalt ratios at 0.05A g -1 Schematic diagram of the electrochemical performance.
[0030] Fig.12 Schematic diagram of the proportion of low-pressure platform areas with different asphalt ratios.
[0031] Fig.13 For HC-30P at 3A g -1 Schematic diagram of the electrochemical performance.
[0032] Fig.14 Schematic diagram of rate performance of different asphalt ratios DETAILED DESCRIPTION
[0033] The present invention proposes a method for preparing a mixed soft and hard carbon material, wherein asphalt is dissolved and filled into the pores of polyphosphazene nanotubes, and then the mixed soft and hard carbon material is obtained by carbonization. The specific preparation method is:
[0034] S1. preparing polyphosphazene nanotubes (PZS);
[0035] S2. Preparation of polyphosphazene nanotube @ asphalt precursor material (PZS@P): dissolving a certain amount of asphalt (Pitch) in an appropriate amount of solvent; then stirring evenly at room temperature and adding a certain mass ratio of polyphosphazene nanotubes; the mass ratio of asphalt to polyphosphazene nanotubes is controlled at 1:2-1:20; continuing to stir so that the dissolved asphalt diffuses into the pores of the polyphosphazene nanotubes and deposits, thereby obtaining the polyphosphazene nanotube @ asphalt precursor material;
[0036] S3, preparation of mixed soft and hard carbon material (HC-XP): The polyphosphazene nanotubes@asphalt precursor material obtained in S2 is carbonized to obtain a mixed soft and hard carbon material powder. The carbonized PZS@P mixture is recorded as HC-XP (X is the content of asphalt in the PZS@P precursor).
[0037] The self-template method is used in step (1) of the preparation method of the mixed soft and hard carbon material. The so-called self-template method is to generate a certain three-dimensional structure as a template during the reaction process, reduce the introduction of external variables, deposit atoms or ions on the template by physical, chemical or biological methods during the reaction process, and remove the template by physical or chemical methods after the reaction to obtain the desired nanostructured material. The nanomaterial prepared by this method has structural characteristics similar to the template cavity. The present invention uses the reaction intermediate product as a template to prepare polyphosphazene nanotubes, and the reactants, namely hexachlorocyclotriphosphazene, 4,4-dihydroxydiphenyl sulfone and acid binding agent triethylamine, are all known to those skilled in the art.
[0038] In step (2) of the preparation method of the mixed soft and hard carbon material, since the polyphosphazene nanotubes have a porous structure, they provide abundant storage space. However, the presence of these micropores increases the specific surface area after carbonization, which will greatly reduce the initial coulomb efficiency. By introducing asphalt, the asphalt can be dissolved into small molecules and diffuse into the pores. After carbonization, it can well fill these pores and shrink in the pores to produce closed pores of suitable size. The asphalt can also form a soft carbon coating on the hard carbon surface to modify surface defects and reduce the specific surface area. Figure 1 As shown, it is the change of specific surface area before carbonization. Figure 4 The change in specific surface area after carbonization. By comparison, it can be seen that the number of 0.7-5 nm open pores in PZS@P and HC-30P is significantly reduced compared to PZS and HC, indicating that the open pores are filled with asphalt and graphitized carbon after asphalt carbonization, and the specific surface area is also significantly reduced. In addition, the mesoporous channels of the material usually have good interconnection. These asphalts are interconnected after being carbonized in the pores to form a three-dimensional interconnected conductive network, which increases the conductivity of the material and can be used in Figure 5 The interconnected graphitized carbon structure is clearly seen in the graphite.
[0039] However, the inventors found that direct solid phase mixing of polyphosphazene and asphalt resulted in obvious two-phase separation after carbonization, indicating that when direct solid phase mixing was performed, asphalt could not be diffused into the pores of polyphosphazene in a molten state. Fig. 9 As shown. In order to improve the uniform dispersion of asphalt, the asphalt is dissolved in the solution into small molecules. These small molecules diffuse into the pores in the liquid and are dispersed more evenly. After carbonization, as shown Fig.10 As shown, there is no particular limitation on the solution, as long as it can dissolve asphalt, such as tetrahydrofuran, N-methylpyrrolidone and toluene. In one embodiment of the present invention, tetrahydrofuran is used as the solvent, and the asphalt is dissolved and diffused into the pores to make the distribution more uniform (such as Fig. 9 and Fig.10 shown).
[0040] In step (3) of the preparation method of the mixed soft and hard carbon material, PZS@P is carbonized. The carbonization temperature has a significant effect on the performance of the final material because the carbonization temperature affects the closed-pore structure and the degree of graphitization, thereby affecting the active sites of the sodium ions. If the temperature is too low, the carbon skeleton cannot grow and rearrange, and fewer closed pores are generated; if the temperature is too high, the disordered carbon will transform into a more ordered state, thereby reducing the size of the closed pores and the interlayer spacing, affecting the transmission of sodium ions. Therefore, it is necessary to optimize the temperature. In the present invention, the carbonization temperature is 1300-1600°C.
[0041] The mixed soft and hard carbon materials prepared by the preparation method of the mixed soft and hard carbon materials can be used in the preparation of negative electrode materials for sodium ion batteries. The preparation method includes: fully mixing and grinding the prepared mixed soft and hard carbon materials, conductive carbon black and sodium alginate in a mass ratio of 7:2:1-8:1:1, then transferring them to a glass bottle, adding an appropriate amount of deionized water and stirring overnight to form a viscous and evenly dispersed slurry, applying it on a copper foil with a scraper of different thicknesses, and then vacuum drying at 80°C for 12 hours, punching out sheets into 12mm as negative electrode materials for sodium ion batteries; cutting the above-mentioned negative electrode materials for sodium ion batteries into circular pole pieces with a diameter of 12mm, and then using positive electrode materials, electrolytes, diaphragms, electrode shells and negative electrode materials to assemble batteries. The selected positive electrode material is a sodium sheet; the diaphragm is Whatman GF / D; the electrolyte is 1M NaPF 6 In DIGLYME = 100 Vol% solution.
[0042] Example 1
[0043] The present invention provides a method for preparing a hybrid soft and hard carbon material and its application in sodium ion batteries, the steps are as follows:
[0044] (1) Preparation of PZS: 0.5 g HCCP (1.44 mmol) and 1.08 g BPS (4.32 mmol) were dissolved in 100 mL tetrahydrofuran to obtain solution A. After magnetic stirring for 30 min, a transparent solution was obtained. Then, 1.31 g TEA (12.96 mmol) was added to solution A. The solution was then ultrasonicated for 10 h at room temperature with an ultrasonic power of 40 kW. After the reaction was completed, the solution was centrifuged and the centrifuged product was washed 3-4 times with acetone and deionized water, respectively, to obtain a white product. Finally, the white product was dried in a vacuum oven overnight to obtain PZS.
[0045] (2) Preparation of PZS@P: 0.1 g of asphalt was dissolved in 20 ml of tetrahydrofuran, followed by magnetic stirring at room temperature for 10 h. After stirring evenly, 1 g of PZS (mass ratio of asphalt to PZS 1:10) was added and magnetic stirring was continued for 10 h to allow the dissolved asphalt to fully diffuse into the pores of PZS and to precipitate. After stirring, the mixture was heated to 80 °C in an oil bath to volatilize the tetrahydrofuran, thereby obtaining PZS@P.
[0046] (3) Preparation of HC-10P: The PZS@P mixture in step (2) is carbonized and recorded as HC-10P (10P is the asphalt content in the PZS@P precursor). The precursor obtained in step (2) is ground evenly and placed in a corundum crucible. The crucible is then placed in a high-temperature tubular furnace and filled with high-purity nitrogen as a protective gas. The temperature is increased at a rate of 2°C / min according to actual conditions to 1400°C for carbonization and kept at this temperature for 1 hour. After the reaction is completed, the mixture is naturally cooled to room temperature. The entire reaction process is carried out in an inert atmosphere. After the reaction is completed, HC-10P powder is obtained.
[0047] (4) Preparation of HC-10P negative electrode: The prepared HC-10P, conductive carbon black and sodium alginate (CMC) were thoroughly mixed and ground in a mass ratio of 8:1:1, then transferred to a glass bottle, added with an appropriate amount of deionized water and stirred overnight to form a viscous and evenly dispersed slurry, which was coated on a copper foil with a 100 μm scraper, then vacuum dried at 80 °C for 12 h, and punched into 12 mm electrode sheets as sodium ion battery negative electrode materials.
[0048] Example 2
[0049] The present invention provides a method for preparing a hybrid soft and hard carbon material and its application in sodium ion batteries, the steps are as follows:
[0050] (1) Preparation of PZS: 0.5 g HCCP (1.44 mmol) and 1.08 g BPS (4.32 mmol) were dissolved in 100 mL tetrahydrofuran to obtain solution A. After magnetic stirring for 30 min, a transparent solution was obtained. Then, 1.31 g TEA (12.96 mmol) was added to solution A. The solution was then ultrasonicated for 10 h at room temperature with an ultrasonic power of 40 kW. After the reaction was completed, the solution was centrifuged and the centrifuged product was washed 3-4 times with acetone and deionized water, respectively, to obtain a white product. Finally, the white product was dried in a vacuum oven overnight to obtain PZS.
[0051] (2) Preparation of PZS@P: 0.3 g of asphalt was dissolved in 50 ml of tetrahydrofuran, followed by magnetic stirring at room temperature for 10 h. After stirring evenly, 1 g of PZS (mass ratio of asphalt to PZS: 3:10) was added and magnetic stirring was continued for 10 h to allow the dissolved asphalt to fully diffuse into the pores of PZS and to precipitate. After stirring, the mixture was heated to 80 °C in an oil bath to volatilize the tetrahydrofuran, thereby obtaining PZS@P.
[0052] (3) Preparation of HC-30P: The PZS@P mixture in step (2) is carbonized and recorded as HC-30P. The obtained PZS@P precursor is ground evenly and placed in a corundum crucible. The crucible is then placed in a high-temperature tube furnace and filled with high-purity nitrogen as a protective gas. The temperature is increased at a rate of 2°C / min according to actual conditions to 1400°C for carbonization and kept at this temperature for 1 hour. After the reaction is completed, the mixture is naturally cooled to room temperature. The entire reaction process is carried out in an inert atmosphere. After the reaction is completed, HC-30P powder is obtained.
[0053] (4) Preparation of HC-30P negative electrode: The prepared HC-30P, conductive carbon black and sodium alginate (CMC) were thoroughly mixed and ground in a mass ratio of 8:1:1, then transferred to a glass bottle, added with an appropriate amount of deionized water and stirred overnight to form a viscous and evenly dispersed slurry, which was coated on a copper foil with a 100 μm scraper, then vacuum dried at 80 °C for 12 h, and punched into 12 mm electrode sheets as sodium ion battery negative electrode materials.
[0054] Example 3
[0055] The present invention provides a method for preparing a hybrid soft and hard carbon material and its application in sodium ion batteries, the steps are as follows:
[0056] (1) Preparation of PZS: 0.5 g HCCP (1.44 mmol) and 1.08 g BPS (4.32 mmol) were dissolved in 100 mL tetrahydrofuran to obtain solution A. After magnetic stirring for 30 min, a transparent solution was obtained. Then, 1.31 g TEA (12.96 mmol) was added to solution A. The solution was then ultrasonicated for 10 h at room temperature with an ultrasonic power of 40 kW. After the reaction was completed, the solution was centrifuged and the centrifuged product was washed 3-4 times with acetone and deionized water, respectively, to obtain a white product. Finally, the white product was dried in a vacuum oven overnight to obtain PZS.
[0057] (2) Preparation of PZS@P: 0.5 g of asphalt was dissolved in 70 ml of tetrahydrofuran, followed by magnetic stirring at room temperature for 10 h. After stirring evenly, 1 g of PZS (mass ratio of asphalt to PZS 1:2) was added and magnetic stirring was continued for 10 h to allow the dissolved asphalt to fully diffuse into the pores of PZS and to precipitate. After stirring, the mixture was heated to 80 °C in an oil bath to volatilize the tetrahydrofuran, thereby obtaining PZS@P.
[0058] (3) Preparation of HC-50P: The PZS@P mixture in step (2) is carbonized and recorded as HC-50P. The obtained PZS@P precursor is ground evenly and placed in a corundum crucible. The crucible is then placed in a high-temperature tube furnace and filled with high-purity nitrogen as a protective gas. The temperature is increased at a rate of 2°C / min according to actual conditions to 1400°C for carbonization and kept at this temperature for 1 hour. After the reaction is completed, the mixture is naturally cooled to room temperature. The entire reaction process is carried out in an inert atmosphere. After the reaction is completed, HC-50P powder is obtained.
[0059] (4) Preparation of HC-50P negative electrode: The prepared HC-50P, conductive carbon black and sodium alginate (CMC) were thoroughly mixed and ground in a mass ratio of 8:1:1, then transferred to a glass bottle, added with an appropriate amount of deionized water and stirred overnight to form a viscous and evenly dispersed slurry, which was coated on a copper foil with a 100 μm scraper, then vacuum dried at 80 °C for 12 h, and punched into 12 mm electrode sheets as sodium ion battery negative electrode materials.
[0060] Example 4
[0061] The present invention provides a method for preparing a hybrid soft and hard carbon material and its application in sodium ion batteries, the steps are as follows:
[0062] (1) Preparation of PZS: 0.5 g HCCP (1.44 mmol) and 1.08 g BPS (4.32 mmol) were dissolved in 100 mL tetrahydrofuran to obtain solution A. After magnetic stirring for 30 min, a transparent solution was obtained. Then, 1.31 g TEA (12.96 mmol) was added to solution A. The solution was then ultrasonicated for 10 h at room temperature with an ultrasonic power of 40 kW. After the reaction was completed, the solution was centrifuged and the centrifuged product was washed 3-4 times with acetone and deionized water, respectively, to obtain a white product. Finally, the white product was dried in a vacuum oven overnight to obtain PZS.
[0063] (2) Preparation of PZS@P: 0.3 g of asphalt was dissolved in 50 ml of water, followed by magnetic stirring at room temperature for 10 h. After stirring evenly, 1 g of PZS (mass ratio of asphalt to PZS: 3:10) was added and magnetic stirring was continued for 10 h to allow the dissolved asphalt to fully diffuse into the pores of PZS and to precipitate. After stirring, the mixture was heated to 80 °C in an oil bath to volatilize tetrahydrofuran, thereby obtaining PZS@P.
[0064] (3) Preparation of HC-30P-1300: The obtained PZS@P precursor was ground evenly and placed in a corundum crucible. The crucible was then placed in a high-temperature tube furnace and passed with high-purity nitrogen as a protective gas. The temperature was raised at a rate of 2°C / min according to the actual situation to 1300°C for carbonization and kept at this temperature for 1 hour. After the reaction was completed, it was naturally cooled to room temperature. The entire reaction process was carried out in an inert atmosphere. After the reaction was completed, HC-30P-1300 powder was obtained.
[0065] (4) Preparation of HC-30P-1300 negative electrode: The prepared HC-30P-1300, conductive carbon black and sodium alginate (CMC) were thoroughly mixed and ground in a mass ratio of 8:1:1, then transferred to a glass bottle, added with an appropriate amount of deionized water and stirred overnight to form a viscous and evenly dispersed slurry, which was coated on a copper foil with a 100 μm scraper, then vacuum dried at 80 °C for 12 h, and punched into 12 mm electrode sheets as sodium ion battery negative electrode materials.
[0066] Comparative Example 1
[0067] (1) Preparation of PZS: 0.5 g HCCP (1.44 mmol) and 1.08 g BPS (4.32 mmol) were dissolved in 100 mL tetrahydrofuran to obtain solution A. After magnetic stirring for 30 min, a transparent solution was obtained. Then, 1.31 g TEA (12.96 mmol) was added to solution A. The solution was then ultrasonicated for 10 h at room temperature with an ultrasonic power of 40 kW. After the reaction was completed, the solution was centrifuged and the centrifuged product was washed 3-4 times with acetone and deionized water, respectively, to obtain a white product. Finally, the white product was dried in a vacuum oven overnight to obtain PZS.
[0068] (2) Preparation of HC: The obtained PZS precursor is ground evenly and placed in a corundum crucible. The crucible is then placed in a high-temperature tube furnace and filled with high-purity nitrogen as a protective gas. The temperature is raised at a rate of 2°C / min according to actual conditions to 1400°C for carbonization and kept at this temperature for 1 hour. After the reaction is completed, the mixture is naturally cooled to room temperature. The entire reaction process is carried out in an inert atmosphere. HC powder is obtained after the reaction is completed.
[0069] (3) Preparation of HC negative electrode: The prepared HC, conductive carbon black and sodium alginate (CMC) were thoroughly mixed and ground in a mass ratio of 8:1:1, then transferred to a glass bottle, added with an appropriate amount of deionized water and stirred overnight to form a viscous and evenly dispersed slurry, which was coated on a copper foil with a 100 μm scraper, then vacuum dried at 80 °C for 12 h, and punched into 12 mm electrode sheets as sodium ion battery negative electrode materials.
[0070] Comparative Example 2
[0071] (1) Preparation of PC: Place commercial asphalt precursor into a corundum crucible, then place the crucible into a high-temperature tube furnace and pass high-purity nitrogen as a protective gas. According to the actual situation, the temperature is raised at a rate of 2°C / min to 1400°C for carbonization and kept at this temperature for 1 hour. After the reaction is completed, the crucible is naturally cooled to room temperature. The entire reaction process is carried out in an inert atmosphere. PC powder is obtained after the reaction is completed.
[0072] (2) Preparation of PC negative electrode: The prepared PC, conductive carbon black and sodium alginate (CMC) were thoroughly mixed and ground in a mass ratio of 8:1:1, then transferred to a glass bottle, added with an appropriate amount of deionized water and stirred overnight to form a viscous and evenly dispersed slurry, which was coated on a copper foil with a 100 μm scraper, then vacuum dried at 80 °C for 12 h, and punched into 12 mm electrode sheets as sodium ion battery negative electrode materials.
[0073] Experimental example
[0074] Performance test of HC-XP, HC and PC materials
[0075] 1. Pore size distribution test: Nitrogen adsorption and desorption tests were performed on HC-30P in Example 1 and HC and PC materials in Comparative Examples 1 and 2 to determine their specific surface area and pore size distribution. All samples were vacuum degassed at 200°C for 6 hours, cooled to room temperature under vacuum and weighed, and then the sample tubes were transferred to the analysis station, and liquid nitrogen was added to the Dewar flask to provide a low-temperature environment for adsorption testing. Nitrogen was used as the adsorption medium and helium was used as the carrier gas. A certain proportion of mixture was performed and adjusted to a predetermined relative pressure level. The equipment model is V-Sorb 4800TP of Guoyi Precision Measurement.
[0076] Figure 1 and Figure 4 The nitrogen adsorption and desorption curves of the HC-30P material of Example 3 and the HC and PC materials of Comparative Examples 1 and 2 are shown respectively. It can be seen from the curve results that the specific surface area of the HC-30P material of Example 3 according to the present invention is greatly reduced compared with the HC of Comparative Example 1, and the reduction is mainly in the specific surface area of the micropore region. The specific surface area of the material calculated by the BET method is 5.8 m 2 g -1 The HC material of Comparative Example 1 is mainly microporous and has a specific surface area of 76.6 m 2 g -1 .
[0077] Figure 2 and Figure 5The pore size distribution curves of the HC-30P material of Example 3 and the HC and PC materials of Comparative Examples 1 and 2 are shown respectively. As can be seen from the figure, the HC-30P material of Example 3 according to the present invention has no obvious pore size distribution, indicating that the number of open pores in each pore size range is small; while the HC material of Comparative Example 1 has obvious micropore distribution, which indicates that the asphalt diffuses into the open pores of the polyphosphazene precursor after dissolution, and these asphalts are retained in the pores during carbonization, increasing the number and volume of closed pores.
[0078] 2. Morphology characterization: Figure 2 SEM images of the HC-XP materials obtained in Examples 1-3 are shown. Figure 1 It can be seen that the HC-XP prepared according to this method agglomerates with the increase of asphalt content, and the carbonized nanotubes are surrounded by asphalt carbon and interconnected. Figure 8 It can be seen from the TEM image in Experimental Example 3 that interconnected short-range ordered graphitized stripes appear inside HC-30P, and the appearance of closed pores can be observed from TEM, while the TEM image in Comparative Example 1 is as follows: Figure 7 As shown, there are no obvious graphite stripes, showing a more disordered state. However, when the asphalt content is greater than 50%, the asphalt will preferentially agglomerate and cannot form an effective surface coating, affecting the performance of the material. Therefore, the optimal asphalt content is 10-50%.
[0079] 3. Structural test: Through the Raman and XPS analysis of the materials of Experimental Examples 1-3 and Comparative Examples 1 and 2, it can be seen that with the increase of asphalt content, the Raman D / I G The value of gradually decreases, indicating a transition to ordering. This is because the asphalt is in a relatively ordered state after carbonization, which can repair the defects in the HC structure. The same pattern is also seen in XPS, with the CC bond content decreasing and the C=C content increasing. This is because CC generally corresponds to a defective sp3 carbon structure, while C=C corresponds to a more ordered sp2 carbon structure. Studies have shown that a suitable ratio of sp2 / sp3 hybridized graphite carbon can form an optimal solid electrolyte interface (SEI) during battery cycling, and HC-30P has the most suitable ratio. The SEI formed is thinner and more uniform, which is beneficial to the transmission of ions and reduces the consumption of irreversible sodium ions, thereby improving the first coulombic efficiency.
[0080] 4. Cycling performance test of sodium ion battery negative electrode: Cycling performance test was conducted on HC-XP in Examples 1 to 3 and HC negative electrode in Comparative Example 1. The specific process is as follows: Battery cycling performance and constant current charge and discharge curve test were tested and analyzed on the Xinwei battery test system. HC-XP and HC negative electrodes were used as working electrodes. They were set to discharge first and then charge and then cycle in sequence. The voltage range was 0.01-2.5V. The results of the cycling performance test of HC-XP negative electrode in Examples 1 to 3 and HC negative electrode in Comparative Example 1 are shown in Figures 11 to 14 Among them, HC-30P prepared based on the present invention has the highest specific capacity, at 0.05A g -1 At a current density of 1.3 Å, the reversible capacity reaches 413 mAh g -1 , and the platform area accounts for 67%, the highest platform ratio among all tested samples, and the first coulombic efficiency is increased from 80% of HC to 88.7% of HC-30P, which shows that it has great commercial prospects and further proves that HC-30P has a good performance in high current 3A g -1 Long cycle test is performed under Fig.13 As shown, even at 3A g -1 At high current density, the capacity remains at 200 mAh g -1 The capacity retention rate after 2500 cycles is 87%. The rate test is carried out at different current densities, such as Fig.14 As shown in Figure 2, HC-30P also has the best specific capacity and is -1 At a current density of 181.5 mAh g -1 . The excellent electrochemical performance of HC-30P mainly comes from the appropriate closed-pore size and the mixed distribution of soft and hard carbon. The appropriate closed-pore size can provide sufficient active sites, thereby increasing the storage capacity of sodium ions, while the mixed distribution of soft and hard carbon reduces surface defects and improves conductivity, promoting the diffusion of sodium ions while reducing the occurrence of side reactions. When the asphalt content is less than 10%, due to the inability to fully fill the open pores, it is impossible to form enough closed pores to provide active sites, and due to the insufficient asphalt, it is also unevenly distributed on the surface of the precursor, resulting in a low first coulomb efficiency. When the asphalt content is greater than 50%, due to excessive asphalt, the asphalt tends to agglomerate itself during the carbonization process, and asphalt is a long-range ordered soft carbon with a small interlayer spacing and fewer closed pores, which cannot provide active sites, resulting in too low capacity. Therefore, the asphalt content of 10-50% is more suitable, and when the asphalt content is 30%, it can provide the largest sodium ion storage active site and the electrochemical performance is optimal.
[0081] The present invention converts open pores into closed pores by preparing a composite carbon material. The synthesized polyphosphazene PZS is used as a precursor. PZS contains a large number of micropores and mesopores, and asphalt can be dissolved in tetrahydrofuran as small molecules. These small molecules can diffuse into the pores of PZS in the solvent and gradually deposit to repair the pores. After drying, the asphalt acts as a "binder" to connect the various nanotubes together. After carbonization, the three-dimensionally interconnected asphalt is carbonized into graphitized carbon, which improves conductivity and promotes the transmission of electrons in the negative electrode material. At the same time, the asphalt has fewer surface defects. After high-temperature carbonization, the asphalt will repair the defects on the HC surface as a surface coating. At the same time, the contraction and rearrangement of the carbon skeleton cause the asphalt and PZS contact surface to form closed pores, which increases the active sites for storing sodium ions, thereby increasing the platform capacity in the low-pressure area. The change in specific surface area after dissolving the asphalt before carbonization can be known through BET, such as Figure 1 As shown in the figure, the surface area and the number of micropores were significantly reduced after coating, indicating that the asphalt diffused into the pores of PZS and repaired the surface defects.
[0082] pass Figure 3 From the SEM images in the figure, it can be found that after carbonization, larger particles appear with the increase of asphalt content. This is because asphalt has strong adhesion at room temperature, which aggregates the individual PZS nanotubes (a, e, i are HC-10P; b, f, j are HC-30P; c, g, k are HC-50P; d, h, l are HC-80P). After carbonization, these asphalt-based graphite carbons can increase the conductivity and shorten the transmission distance of sodium ions, which is more conducive to the diffusion of sodium ions. The specific surface area after agglomeration is also increased from the original 76.6m 2 g -1 Reduced to 5.8m 2 g -1 ,
[0084] By adjusting the asphalt content, the sp2 / sp3 content distribution in HC-XP after carbonization can also be adjusted. As the asphalt content increases, the ratio of sp2 / sp3 hybridized graphite carbon on the surface changes. A higher ratio of sp2 hybridized graphite carbon contributes to higher electron transmission capacity, but the capacity is limited due to fewer defects; a higher ratio of sp3 hybridized amorphous carbon can obtain more defect structures, making larger storage capacity possible, but these defects will cause the first coulomb efficiency ICE to decrease. In order to break the trade-off between ICE and capacity, the sp2 / sp3 structure should be adjusted to a balanced state to obtain the optimal solid electrolyte interface (SEI) during the battery cycle and achieve the optimal ICE and sodium ion storage capacity.
[0085] In addition, since the soft and hard carbon composite materials of the present invention have a higher closed-pore content, sp2 / sp3 synergistic balance and surface coating modification, the specific capacity, rate performance and cycle life of the sodium ion battery negative electrode material based on the material of the present invention are significantly improved, and excellent cycle performance is also obtained after assembling the full battery, demonstrating its practicality.
[0086] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited thereto, and various changes can be made within the knowledge scope of technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A method for preparing a mixed soft and hard carbon material, characterized in that: The asphalt is dissolved and filled into the pores of the polyphosphazene nanotubes, and then carbonized to obtain a mixed soft and hard carbon material.
2. The method for preparing a mixed soft and hard carbon material according to claim 1, characterized in that: The specific preparation method is: S1. preparing polyphosphazene nanotubes; S2. Preparation of polyphosphazene nanotube @ asphalt precursor material: dissolving a certain amount of asphalt in an appropriate amount of solvent; then stirring evenly at room temperature and adding a certain mass ratio of polyphosphazene nanotubes; the mass ratio of asphalt to polyphosphazene nanotubes is controlled at 1:2-1:20; continuing to stir so that the dissolved asphalt diffuses into the pores of the polyphosphazene nanotubes and deposits, thereby obtaining the polyphosphazene nanotube @ asphalt precursor material; S3, preparing mixed soft and hard carbon materials: carbonizing the polyphosphazene nanotube@asphalt precursor material obtained in S2 to obtain mixed soft and hard carbon material powder.
3. The method for preparing a mixed soft and hard carbon material according to claim 2, characterized in that: The preparation method of polyphosphazene nanotubes in S1 is as follows: a certain proportion of hexachlorocyclotriphosphazene and 4,4-dihydroxydiphenyl sulfone are dissolved in an appropriate amount of tetrahydrofuran, stirred to dissolve into a transparent solution, then a proper amount of acid binding agent is added, and then ultrasonicated at 40°C for 10 hours. After the reaction is completed, the polyphosphazene nanotubes are washed with acetone and deionized water respectively, centrifuged, and then dried to obtain the polyphosphazene nanotubes.
4. The method for preparing a mixed soft and hard carbon material according to claim 2, characterized in that: The solvent in S2 is one or more of tetrahydrofuran, N-methylpyrrolidone, benzene, toluene or carbon tetrachloride, the amount of the solvent is 20-100 ml, and the solution concentration is 5 g / L-10 g / L.
5. The method for preparing a mixed soft and hard carbon material according to claim 4, characterized in that: The solvent in S2 is tetrahydrofuran, and after the magnetic stirring is completed, the mixture is heated to 50°C-100°C in an oil bath to volatilize the tetrahydrofuran.
6. The method for preparing a mixed soft and hard carbon material according to claim 2, characterized in that: In S2, both stirring steps were performed with magnetic stirring for 10 h.
7. The method for preparing the hybrid soft and hard carbon material and the application thereof in sodium ion batteries according to claim 2, characterized in that: The carbonization treatment method in S3 is: grind the polyphosphazene nanotube @ asphalt precursor material evenly and put it into a corundum crucible, then put the crucible into a high-temperature tubular furnace and pass high-purity nitrogen as a protective gas, and heat it at a rate of 1-5℃ / min according to actual conditions, raise it to 1300-1600℃ for carbonization and keep it warm for 1-3h, and naturally cool it to room temperature after the reaction is completed. The whole reaction process is carried out in an inert atmosphere, and the mixed soft and hard carbon material powder is obtained after the reaction is completed.
8. Application of sodium ion battery of mixed soft and hard carbon materials, characterized in that: The mixed soft and hard carbon material prepared by the method for preparing the mixed soft and hard carbon material according to claim 2 is applied to the preparation of negative electrode materials for sodium ion batteries.
9. The application of the mixed soft and hard carbon material in sodium ion battery according to claim 8, characterized in that: The preparation method comprises: fully mixing and grinding the prepared mixed soft and hard carbon material, conductive carbon black and sodium alginate in a mass ratio of 7:2:1-8:1:1, then transferring to a glass bottle, adding an appropriate amount of deionized water and stirring overnight to form a viscous and evenly dispersed slurry, coating it on a copper foil with a scraper of different thicknesses, then vacuum drying at 80°C for 12 hours, and punching into 12mm sheets as a negative electrode material for a sodium ion battery; cutting the above-mentioned negative electrode material for a sodium ion battery into circular electrodes with a diameter of 12mm, and then using a positive electrode material, an electrolyte, a diaphragm, an electrode shell and a negative electrode material to assemble a battery.
10. Application of the mixed soft and hard carbon material in sodium ion battery according to claim 9, characterized in that: The selected positive electrode material is sodium sheet; the separator is Whatman GF / D; and the electrolyte is 1M NaPF6 in DIGLYME=100Vol% solution.
Citation Information
Patent Citations
Organic tin phosphide / graphite oxide composite material used for sodium ion battery negative electrode
CN109698326A
Nitrogen and phosphorus doped Si / CNTs / C composite lithium ion battery negative electrode material and preparation method thereof
CN113644250A
Preparation method of asphalt-based composite hard carbon for sodium ion battery
CN117509608A
Preparation method of high-concentration heteroatom-doped mesoporous carbon nanotube material and application of high-concentration heteroatom-doped mesoporous carbon nanotube material in lithium-sulfur battery
CN119118115A
Phosphazene compound-based elastic polymer-encapsulated anode particles for lithium batteries and method of manufacturing
WO2022170334A1